1994
DOI: 10.1159/000213617
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Paroxetine in the Elderly

Abstract: Depression in the elderly is an increasingly prevalent problem affecting some 15% of the elderly population and can be difficult to diagnose and treat. Complicating factors include poor compliance, the high frequency of concomitant disease, and the alterations in drug absorption and metabolism with age. This paper reviews controlled studies of the treatment of depression in elderly patients using paroxetine, a selective serotonin reuptake inhibitor. The studies demonstrate that paroxetine has efficacy in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Treatment is also more likely to be complicated by adverse side effects and drug interactions than in younger patients. Studies in the elderly have shown paroxetine to be effective and well tolerated (Dunner, 1994). It has also been shown to have no disruptive effect on tests of cognitive and psychomotor performance in healthy (Kerr et al, 1992) or depressed elderly patients (Nebes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is also more likely to be complicated by adverse side effects and drug interactions than in younger patients. Studies in the elderly have shown paroxetine to be effective and well tolerated (Dunner, 1994). It has also been shown to have no disruptive effect on tests of cognitive and psychomotor performance in healthy (Kerr et al, 1992) or depressed elderly patients (Nebes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The current recommended first-line therapy for depression in later life is a serotonin selective re-uptake inhibitor (SSRI) because in comparison to tricyclic antidepressants like nortriptyline, SSRIs are safer in overdose, better tolerated, and do not require monitoring blood levels or EKG analysis prior to initiation of therapy [for review, see Montgomery, 1998;Dunner, 1994]. Multiple clinical trials have found similar efficacy between SSRIs and TCAs in the acute treatment of geriatric depression, with SSRIs being better tolerated [for review, see Schneider, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…22 Elderly depressed patients may exhibit more cognitive impairment and social isolation and may complain less of dysphoric mood. The presentation of symptoms in an elderly depressed patient may be similar to or may differ from a younger depressed patient.…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%
“…The presentation of symptoms in an elderly depressed patient may be similar to or may differ from a younger depressed patient. 22 Elderly depressed patients may exhibit more cognitive impairment and social isolation and may complain less of dysphoric mood. 23 The elderly may also be more somatically focused, experience a higher level of fatigue and psychomotor retardation, and complain more about loss of interest in usual activities.…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%